Multiplexing real time video services - Simón, María (1997)
Statistical Bit Rate (SBR) ATM capability is considered a good option for supporting Variable Bit Rate (VBR) services. However, its study is somewhat in lag compared with Deterministic Bit Rate (DBR) or Available Bit Rate (ABR) capabilities. The de nition of a general Call Acceptance Control (CAC) function is di cult to state for SBR. We present some results regarding the multiplexing of real time data streams, mainly from interactive video services, which are naturally VBR and therefore candidates to use the SBR capability. It is shown that image quality is improved by using SBR instead of DBR. The coder design does not become more complicated. In fact, it remains the same. We propose a statistical model for the tra c generated by such video sources. The delays introduced by a switch are studied following two approaches. Exact bounds are found for a worst case situation, indicating a very low statistical gain. However, simulations show that these bounds are too pessimistic since the worst case very rarely occurs. A very high mean load can be reached with acceptable delays. Indeed, the statistical gain is found to be signi cant. The CAC for this kind of service may be simple because, even assuming pessimistic gures, the burstiness for a real-time video data stream appears to be low.